The effects of different UV‐B radiation intensities on morphological and biochemical characteristics in Ocimum basilicum L. (11th September 2012) - Sakalauskaitė, Jurga; Viskelis, Pranas; Dambrauskienė, Edita; Sakalauskienė, Sandra; Samuolienė, Giedrė; Brazaitytė, Aušra; Duchovskis, Pavelas; Urbonavičienė, Dalia
Abstract BACKGROUND: The effects of short‐term ultraviolet B (UV‐B) irradiation on sweet basil (Ocimum basilicum L. cv. Cinnamon) plants at the 3–4 leaf pair and flowering stages were examined in controlled environment growth chambers. Plants were exposed to 0 (reference), 2 and 4 kJ UV‐B m−2 day−1 over 7 days. RESULTS: Exposure of basil plants to supplementary UV‐B light resulted in increased assimilating leaf area, fresh biomass and dry biomass. Stimulation of physiological functions in young basil plants under either applied UV‐B dose resulted in increased total chlorophyll content but no marked variation in carotenoid content. At the flowering stage the chlorophyll and carotenoid contents of basil were affected by supplementary UV‐B radiation, decreasing with enhanced UV‐B exposure. Both total antioxidant activity (2, 2‐diphenyl‐1‐picrylhydrazyl free radical assay) and total phenolic compound content were increased by UV‐B light supplementation. Young and mature basil plants differed in their ascorbic acid content, which was dependent on UV‐B dose and plant age. UV‐B radiation resulted in decreased nitrate content in young basil plants (3–4 leaf pair stage). CONCLUSION: These results indicate that the application of short‐exposure UV‐B radiation beneficially influenced both growth parameters and biochemical constituents in young and mature basil plants. © 2012 Society of Chemical Industry